Вплив високотемпературного вiдпалу на структуру та край власного поглинання тонкоплiвкового кремнiю, легованого оловом - Rudenko, R. M.; Voitovych, V. V.; Kras’ko, M. M.; Kolosyuk, A. G.; Kraichynskyi, A. M.; Yukhymchuk, V. O.; Makara, V. A. (Publishing house "Academperiodika", 2018)
Influence of isochronal annealing in the range of 350–1100 oC on the structural properties and the intrinsic absorption edge in thin silicon films doped with tin (a-SiSn) has been studied. It is found that as-deposited a-SiSn films with a tin content of about 4 at.%, unlike undoped a-Si ones, contain silicon nanocrystals with a crystallite size of about 4 nm and a crystalline fraction of about 65%. It is shown that, in the course of isochronal annealing of a-SiSn specimens in the interval of 350–1100 oC, the size of silicon nanocrystals in the amorphous matrix gradually increases to about 7 nm, and the fraction of crystalline phase to about 100%. Crystallization in undoped a-Si is observed only after the annealing at temperatures above 700 oC. The influence of tin on the optical band gap in a-Si as a function of the isochronal annealing temperature is analyzed.